Varieties of volatility - Benjamin Lee (Finance and Society, 2023)
This article explores the quantitative and qualitative dimensions of volatility and their implications for cultural analysis in a range of fields. From quantitative finance, it takes the notion of 'delta-hedging', the suspension or neutralization of directionality to get access to volatility, and applies this to qualitative areas such as surfing, dance, cinema, and language.
Keywords: 300; Black-Scholes; delta-hedging; directionality; metaphor; metonymy; rhetoric; Volatility